Effect of male pig immunocastration on physical and chemical characteristics of Teruel dry-cured hams - PÉREZ-CIRIA, Leticia; RIPOLL, Guillermo; SANZ, María Á.; BLANCO, Mireia; LATORRE, Maria A. (Spanish Journal of Agricultural Research, 2023)
Aim of study: To evaluate the effect of the type of male castration (surgical vs. immunological) on the characteristics of Teruel dry-cured hams.            Area of study: Teruel and Zaragoza (Spain).            Material and methods: A total of 14 dry-cured hams from Duroc × (Landrace × Large White) male pigs intended for the Spanish Protected Designation of Origin ˈTeruel hamˈ were used. Half of them belonged to surgical castrated males (SCM) and the other half to immunocastrated males (IM). Ham weight losses during processing, physical and chemical characteristics were analyzed.            Main results: There were no differences (p>0.05) due to the type of castration in ham weight losses throughout processing, thickness of subcutaneous fat, marbling, maximum stress and intramuscular fatty acid profile. However, hams from IM presented lower (p<0.05) chroma than those from SCM. The type of castration had limited influence on chemical composition; only potassium nitrate and retinol contents were affected (p<0.05), being lower in IM than in SCM. For volatile compounds, IM showed lower (p<0.05) percentages of total alcohols and sulfur compounds and higher (p=0.012) proportion of total acids than SCM. All the hams had negligible androstenone content but IM presented higher (p<0.05) skatole and indole concentrations than SCM, being these levels low.            Research highlights: The type of castration in male pigs seems to have scarce influence on the quality of Teruel dry-cured hams, and therefore, immunocastration could be considered as a possible alternative to surgical castration.